Electromyographic methods to determine muscle groups to affect sports results in speed climbing - Voronov, A. V.; Kvashuk, P. V.; Voronova, A. A.; Krasnoperova, T. V. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to identify muscles that provide the increase of rates in speed climbing. For this purpose, we used the SportLab hardware-software complex (Russia) consisting of an 8-channel telemetric electromyograph and a video camera. The experiment involved 10 climbers (qualified MS - CMS - I Class) including 4 males and 6 females. The athletes ran the distance at slow, average and maximum speed. The distance speed was picked individually. The distance time was registered using the video camera (frame rate - 50 Hz). The beginning of the first movement was taken as a zero point (start), the touch of a control point - as finish. The subjects performed at least 2 successful (without disruption) attempts at each speed rate. The rest breaks between the races were 8-10 min. Based on the registration and analysis of the electromyographic activity data, we determined the muscles influencing the rates in sport climbing. The data obtained showed that regardless of the athletes` sports qualification there are two muscle groups affecting the sports results: m. gastrocnemius medialis and m. biceps brahii. The significant increase in the average EMG amplitude of some muscles suggests that these muscles are the "leading" ones when approaching record speeds. In this study, these are m. gastrocnemius medialis and m. trapezius.